Concentration polarization distribution along Pd-based membrane reactors: A modelling approach applied to Water-Gas Shift. (30th January 2016) - Caravella, Alessio; Melone, Leonardo; Sun, Yu; Brunetti, Adele; Drioli, Enrico; Barbieri, Giuseppe
Abstract: In this work, an improved membrane characterization, computational fluid dynamic (CFD) simulations of inert particle beds, and simulations of a membrane reactor for Water Gas Shift (WGS) are coupled together to evaluate the concentration polarization distribution along Pd-based membrane reactors. To perform this investigation, first a 3.6 μm-thick Pd75 Ag25 -membrane is characterized using experimental data from the literature as input to an improved approach allowing the non-ideality of internal diffusion to be quantitatively evaluated as a function of hydrogen partial pressure. Then, CFD simulations of a particle bed composed of regular arrays of mono-disperse spherical particles are carried out, showing that the velocity field between particles and membranes contributes to enhance the mass transfer towards the membrane surface. Finally, after validating a 1D-1D reactor model by literature experimental data in terms of both conversion and recovery index vs. feed pressure, simulations of concentration polarization coefficient ( CPC ) profiles along the reactor are performed. These profiles allow a clearly identification of the reactor zones where polarization is higher, providing useful information to minimize the polarization influence on reactor performances. Graphical abstract: Highlights: Concentration polarization is studied for H2 permeation through Pd-membranes. The effect of particle arrays on concentration polarization is investigated by CFD. Concentration polarization profiles along WGS reactor are calculated. Profiles allow identifying the reactor zones where polarization is higher.